Factors Affecting the Retention Value of Drug Addict Patients in Methadone Maintenance Therapy - Siswidiasari, Arifani; Neni Probosiwi; Nur Fahma Laili; Tsamrotul Ilmi; Prayoga Ferry Yuniarto; Anak Agung Indah Krisnadewi; Oktaviarika Dewi H (PT FORMOSA CENDEKIA GLOBAL, 2024)
Methadone is a synthetic drug belonging to the opiate class that is given in oral dosage form to patients as a substitute therapy for opioid addiction. Methadone was chosen as the main substitution therapy because it has an effect resembling morphine and cocaine with a longer working life so that it can be given once a day which is used by drinking. This study aims to determine the factors that affect the retention value of drug addict patients in methadone maintenance therapy at Bangil Health Center. This study was conducted retrospectively, taking medical record data of patients who followed methadone maintenance therapy selected by consecutive sampling. Data obtained as many as 35 patients. The results of demographic data showed the most male sex 33 people (94.3%), aged 26-35 years 22 (62.9%), SMA 29 (82.9%), working 35 (100%), married 27 (77.1%), opium 35 (100%), amphetamines 26 (74.29%), alcohol 33 (94.29%) and tobacco 33 (94.29%). The highest initial dose was 30-50mg, 23 people (65.7%), the smallest maintenance dose <60mg, 33 people (94.3%) and the largest maintenance dose >120mg, 24 people (68.6%). The retention value of patients < 6 months is 7 people (20%) and > 6 months 28 people (80%)